2022
DOI: 10.21037/atm-21-6648
|View full text |Cite
|
Sign up to set email alerts
|

DTL promotes melanoma progression through rewiring cell glucose metabolism

Abstract: Background: To investigate the role of DTL in the development of skin cutaneous melanoma (SKCM) and possible mechanisms. Methods:We examined the expression of DTL in SKCM in The Cancer Genome Atlas (TCGA) and Oncomine database and analyzed the relationship between DTL expression and melanoma prognosis.Furthermore, we silenced the DTL gene by RNA interference in A375 cells and investigated the effect of DTL silencing on the biological function of melanoma cells. Results:The expression of DTL in SKCM was upregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“… Yang et al (2019) suggested that DTL can be regarded as an indicator of poor prognosis in acral melanoma patients. DTL could play an important role in promoting melanoma cell growth and glucose metabolism, possibly through activation of the MYC target pathway ( Lu et al, 2022 ). In the present study, we found that overexpressed DTL was closely associated with worse survival outcomes in cutaneous melanoma patients.…”
Section: Discussionmentioning
confidence: 99%
“… Yang et al (2019) suggested that DTL can be regarded as an indicator of poor prognosis in acral melanoma patients. DTL could play an important role in promoting melanoma cell growth and glucose metabolism, possibly through activation of the MYC target pathway ( Lu et al, 2022 ). In the present study, we found that overexpressed DTL was closely associated with worse survival outcomes in cutaneous melanoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…As previously reports, overexpression of DTL has been found in many cancers and correlated with poor prognosis of cancer patients. In vitro experiments revealed that DTL overexpression promoted the proliferation, migration and invasion of cervical and breast cancer cell lines [ 15 , 25 ], while knockdown of DTL attenuated the growth of cancer cells [ 23 , 25 ]. Hence, the DTL gene might be a potential therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…GINS2 promoted cell proliferation, migration, invasion, and EMT via modulating PI3K/Akt and MEK/ERK signaling pathways [ 54 ], GINS2 knock-down stimulated inflammation and apoptosis in microglia [ 55 ]. DTL, a homolog of E3 ubiquitin ligase that belongs to the DCAF protein family, was reported to enhance the motility, proliferation, and invasion of cancer cells [ 56 , 57 ], and also significantly decrease total glucose consumption and lactate production [ 58 ]. ELANE, a factor that contributes to a protease-antiprotease imbalance and may cause inflammatory lung illnesses [ 59 ], induces autophagy, which in turn induces lung epithelial cell apoptosis and pulmonary emphysema through the overexpression of PGF [ 60 ].…”
Section: Discussionmentioning
confidence: 99%